SUSTAINABLE CEMENT COMPOSITES REINFORCED WITH ERYTHRINA POEPPIGIANA NANOFIBRILS AND INDUSTRIAL WASTE: PHYSICAL-MECHANICAL PERFORMANCE AND MICROSTRUCTURAL ANALYSIS (Editora Impacto Científico, 2025)
This study explores sustainable alternatives for fiber cement by replacing asbestos and valorizing industrial byproducts. An extruded cement composite was produced using cellulose micro/nanofibrils (MNFs) from Erythrina poeppigiana and alkaline residues (Dregs) from the pulp and paper industry. After curing, the specimens were immersed in an ethylene vinyl acetate (EVA) solution, forming an external polymeric coating that protects the lignocellulosic fibers. The optimized composite (EVA2) achieved a Modulus of Rupture (MOR) of 8.7 MPa and a Modulus of Elasticity (MOE) above 4.9 GPa, while water absorption decreased by up to 36% versus the untreated control. SEM analysis confirmed EVA’s role as a physical barrier, improving matrix–fiber cohesion and reducing porosity. The results demonstrate the technical and environmental feasibility of a high-performance fiber cement for civil construction.DOI: https://doi.org/10.56238/edimpacto2025.090-067